2016
DOI: 10.3390/sports4040047
|View full text |Cite
|
Sign up to set email alerts
|

Muscle- and Mode-Specific Responses of the Forearm Flexors to Fatiguing, Concentric Muscle Actions

Abstract: Background: Electromyographic (EMG) and mechanomyographic (MMG) studies of fatigue have generally utilized maximal isometric or dynamic muscle actions, but sport- and work-related activities involve predominately submaximal movements. Therefore, the purpose of the present investigation was to examine the torque, EMG, and MMG responses as a result of submaximal, concentric, isokinetic, forearm flexion muscle actions. Methods: Twelve men performed concentric peak torque (PT) and isometric PT trials before (prete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 58 publications
(73 reference statements)
1
8
0
Order By: Relevance
“…Furthermore, MMG amplitude and MMG mean power frequency values were greater at pretest, posttest, and recovery during the eccentric PT and concentric PT than MVIC muscle actions. These findings were also consistent with previous investigations [15,16] that have examined MMG responses for dynamic versus static muscle actions. In conjunction with previous investigations [15,16], the findings of the present study suggested that dynamic muscle actions may have resulted in greater intracellular and extracellular fluid turbulence, which caused greater muscle perturbations and increased the MMG values [4].…”
Section: Neuromuscular Responsessupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, MMG amplitude and MMG mean power frequency values were greater at pretest, posttest, and recovery during the eccentric PT and concentric PT than MVIC muscle actions. These findings were also consistent with previous investigations [15,16] that have examined MMG responses for dynamic versus static muscle actions. In conjunction with previous investigations [15,16], the findings of the present study suggested that dynamic muscle actions may have resulted in greater intracellular and extracellular fluid turbulence, which caused greater muscle perturbations and increased the MMG values [4].…”
Section: Neuromuscular Responsessupporting
confidence: 92%
“…The fatigue-induced decreases in EMG mean power frequency from pretest to posttest for all three modes of muscle actions supported the fatiguing nature of the 50 repeated, submaximal, eccentric muscle actions. Specifically, fatiguing exercise has been associated with decreases in EMG mean power frequency that may reflect the effect of the accumulation of metabolic byproducts on muscle fiber action potential conduction velocity [15,16,18]. The increases in EMG mean power frequency at recovery may have reflected the clearance of metabolic byproducts or increases in muscle temperature [1].…”
Section: Neuromuscular Responsesmentioning
confidence: 99%
“…For MVIC, however, the bilateral, unilateral right leg, and unilateral left leg fatiguing tasks resulted in non-significant PF in the exercising legs (decreases of approximately 14, 10, and 18%, respectively.) Previous studies (Byrne et al, 2001;Camic, 2011;Hill et al, 2016;Thompson et al, 2015) have reported conflicting evidence for quantifying PF from the PT and MVIC responses to various modes of fatiguing tasks. For example, Thompson et al, (2015) found that following a fatiguing, intermittent, isometric task, concentric PT recovered to the pre-fatigued level more quickly than did MVIC.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the purpose of this study was to examine: 1) Mode-specific testing responses to isokinetic fatigue; 2) differences in PF between bilateral and unilateral leg extensions; and 3) the effects of fatiguing, unilateral, dynamic leg extensions on contralateral leg extension isokinetic PT and MVIC. Based on previous findings, it was hypothesized that there would be similar decreases in PT and MVIC following bilateral, as well as, unilateral muscle actions (Byrne et al, 2001;Camic, 2011;Hill et al, 2016), that unilateral muscle actions would result in greater decreases in PT and MVIC than bilateral muscle actions (Anders et al, 2020b;Matkowski et al, 2011;Rossman et al, 2012Rossman et al, , 2014 and that fatiguing, maximal, unilateral leg extensions would decrease contralateral PT and MVIC.…”
Section: Introductionmentioning
confidence: 99%
“…Li and Hong found when stroke patients took negative-heeled shoes during walking the sEMG amplitudes of GS and BF increased, accompanied by greater knee flexion [ 14 ]. Other studies reported that it was the GS but not the BF that exhibited reduced sEMG amplitude and frequency with decreased knee motion in post-stroke gait [ 15 , 16 ]. These studies inspired us that to further examine the amplitude and frequency information underlying the sEMG signals of the involved muscles would help better understand the causes and solutions of stiff-knee gait in post-stroke patients.…”
Section: Introductionmentioning
confidence: 99%